The use of a balanced system of indicators for the management of construction enterprises - Sotnikova, Irina (Technology audit and production reserves, 2017)
The object of research is a balanced system of indicators (BSI), which is evaluated from the standpoint of its ability to use in the management of construction enterprises, taking into account the current conditions of their functioning in the market. During the research, it is determined that the model of the balanced system of indicators functions only within the limits of the indicated indicators, the choice of which is limited and does not take into account possible changes in the competitive environment. That is why the enterprise, when using the mechanism, should additionally carry out an assessment of possible changes and take into account the subjectivity of a part of the indicators. But for Ukrainian construction companies there is a possibility to take on the experience of foreign countries in introducing BSI and assessing the effectiveness of its use in the practical activities of foreign enterprises. BSI creates the necessary information basis for decision-making for virtually all functions of enterprise management: forecasting, planning, analysis, control and motivation. The implementation of most of the listed functions requires the availability of appropriate information support. The existing approaches to the definition of models of estimation of the efficiency of activity of construction enterprises are analyzed and the main advantages and disadvantages of existing models are substantiated. For construction companies it is suggested to use in practical terms the concept of the strategy of enterprise development on the basis of a balanced system of indicators by determining the main goals, objectives and principles. Within the framework of this work, the evaluation of the activities of Ukrainian construction companies is based on the assumption that the most problematic are, as a rule, the following business processes: preparation of production; marketing; strategic planning; finances; HR (Human Resources). The expediency of using the methodological approach to the assessment of the effectiveness of management of construction enterprises, in which the matrix of business process distribution is based on the definition of the value of the II (index of importance) and the index of problem (IP), is grounded. The mechanism of stimulation of the company’s employees in forming the development strategy based on a balanced system of indicators contributes to the involvement of employees in making decisions in the company’s activities, the setting of clear objectives and fair remuneration standards.